1991
DOI: 10.1111/j.1365-2338.1991.tb00451.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of crop rotation on Globodera rostochiensis and on potato yield1

Abstract: A crop rotation field study was conducted in 1981–1989 to assess the effect of six crop rotation sequences on a soil population of potato cyst nematode (PCN), Globodera rostochiensis, and on potato yield. In the plots with potato monoculture, the tuber yield decreased from 35 to 4.6 t ha−1. All other cropping systems maintained the yield at the original or an even higher level. In monoculture, the population density of the nematode was raised during the first 3 years from 0.1 to 265 larvae g−1 soil, and the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…Levitessään laajalle alueelle peruna-ankeroinen aiheuttaa satotappioita ja heikentää perunantuotannon kannattavuutta. Suomen olosuhteissa tehdyissä kokeissa (Tiilikkala 1991) on havaittu, että perunaankeroissaastunta voidaan välttää, jos perunaa viljellään samalla peltolohkolla harvemmin kuin joka kolmas vuosi. Kun peruna-ankeroisia ilmestyy peltolohkolle, ne lisääntyvät vähitellen, jos perunaa viljellään useampina peräkkäisinä vuosina.…”
Section: Johdantounclassified
“…Levitessään laajalle alueelle peruna-ankeroinen aiheuttaa satotappioita ja heikentää perunantuotannon kannattavuutta. Suomen olosuhteissa tehdyissä kokeissa (Tiilikkala 1991) on havaittu, että perunaankeroissaastunta voidaan välttää, jos perunaa viljellään samalla peltolohkolla harvemmin kuin joka kolmas vuosi. Kun peruna-ankeroisia ilmestyy peltolohkolle, ne lisääntyvät vähitellen, jos perunaa viljellään useampina peräkkäisinä vuosina.…”
Section: Johdantounclassified
“…Marzin (1991) showed that chemical alone was not effective against potato cyst nematodes and must be accompanied by planting a resistant cultivar. Also, Tiilkikkala, (1991) showed that nematicide treatment did not control the nematode population but prevented yield loss.…”
Section: Chemiealsmentioning
confidence: 99%
“…The effectiveness of a rotation is dependent on several factors like temperature, spontaneaus hatch, age of the cysts, field site, etc. Tiilkikkala (1991) showed that planting potatoes once in three years and altemating susceptible and resistant cultivars reduced the population drastically. In England, demonstrated that 11 years of nonhast were necessary to reduce the population level low enough that one year of susceptible host would not increase it above the pre-nonhost level.…”
Section: Rotationmentioning
confidence: 99%
“…Since the beginning of the 19705,PCN has been the most harmful pest ofpotatoes in Finland. Magnusson (1987) and Tiilikkala (1987Tiilikkala ( , 1991) have studied the biological and physical factors affecting the success of G. rostochiensis. In Finland, the whole life cycle of G. rostochiensis requires over 600 day degrees above 4.4°C.…”
Section: Introductionmentioning
confidence: 99%